Study on the mechanical property, water absorption, and acid resisitance of steel and polypropylene hybrid fiber reinforced recycled aggregate concrete - Ramalingam Vijayalakshmi; Shainsha Javith; Harshitha Madhuru; Ramadoss Oshiyana (Građevinski Materijali i Konstrukcije, 2024)
This study aims to develop a sustainable solution in the construction industry by incorporating recycled aggregate (RA) into concrete, partially replacing natural gravel aggregate, and enhancing the strength of RA concrete through the addition of hybrid s The study investigates the effect of steel and polypropylene hybrid s on the mechanical and durability properties of recycled aggregate concrete (RAC). The research was carried out in three phases/mixes. The first mix is with different proportions of recycled aggregate (25% and 50%). The second mix is recycled aggregate concrete with only macro-steel , and the third mix is recycled aggregate concrete with different proportions of macro-steel and micro-polypropylene . Mechanical and durability properties were investigated in all three types of concrete mixes and compared with the control mix. The study concluded that the mechanical properties of hybrid fiber reinforced recycled aggregate concrete (HFRRAC) are dependent on the amount of recycled aggregate, proportions, and type. The macrosteel fibers with high elasticity modulus and stiffness improve the concrete's strength and toughness. The increase in content affects the workability of - reinforced concrete. Synthetic microfibers with excellent ductility and dispersion improve concrete's mechanical properties and durability. Synthetic microfibers when used along with macro-steel improve both mechanical properties and durability characteristics.